2021
DOI: 10.1021/acs.energyfuels.1c02308
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Mechanical Deformation Characteristics of Lithium Iron Phosphate Pouch Battery Modules under Overcharge Conditions

Abstract: Lithium iron phosphate (LFP) pouch batteries are likely to swell under overcharge conditions, failing the module structure. An overcharge experiment was carried out on an LFP battery module composed of 72 LFP pouch cells. The experimental results show that the pouch LFP cell has a large deformation even at a low temperature (below ∼60 °C), and the deformation mainly occurs during the overcharge voltage plateau period. After overcharge, the average temperature increase of the module is 46 °C, and the overcharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Activated or released lattice oxygen can undergo reactions with alkyl carbonate electrolytes, producing additional gaseous byproducts such as CO 2 and CO (Fig. 8(a-e)) [141,153,154].…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…Activated or released lattice oxygen can undergo reactions with alkyl carbonate electrolytes, producing additional gaseous byproducts such as CO 2 and CO (Fig. 8(a-e)) [141,153,154].…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…Inducing factors of battery thermal runaway can be summarized as follows: mechanical abuse (puncture, extrusion, and collision), electrochemical abuse (internal short circuit, overcharging, and overdischarging), and thermal abuse (local overheating and high ambient temperature). , As shown in Figure , there exists a certain relationship among these three abusing conditions, which can be ultimately developed to thermal abuse and consequently cause the thermal runaway of batteries: (1) Mechanical abuse will lead to battery deformation and then induce the occurrence of internal short circuit, that is, electrical abuse; (2) electrical abuse will release Joule heat and chemical reaction heat, further resulting in thermal abuse; (3) the temperature rise caused by thermal abuse will induce the thermal runaway chain reaction of a lithium-ion battery. In essence, battery thermal runaway is a positive feedback cycling process of energies.…”
Section: Thermal Runaway Of Lithium Batteries and Generation Mechanis...mentioning
confidence: 99%
“…Swollen pouch cell issues have been reported on various consumer electronics products such as phones and laptops, causing the device not to operate and the trackpad, screen, or outer cases of the devices to deform, pop open, or fracture (Puls Technologies Inc, 2019;Androidcentral, 2020). Sun et al (2021) showed that the contact pressure of the swollen cells with 278% volume increase on the surrounding components was up to 28 N/mm 2 . The swelling can compromise the waterproof or water-resistant level of the device (Dube, 2018).…”
Section: Case Studies Of Consumer Electronics Products Affected By Po...mentioning
confidence: 99%